KAJIAN TENTANG KUALITAS AIR FOUNTAIN (Studi Kasus Air Fountain di Taman Bungkul Kota Surabaya) - Yuliana Ngasarotun; Narwati .; Imam Thohari (Poltekkes Kemenkes Surabaya, 2013)
People are doubtful to drink from water fountain provided in amusement parks. In addition, itwas whose has the contamination to other users. It was occured becausethe controllers to the faucet ofdrinking water. This research is aimed at studying water quality of a drinking fountain, before and afterthe onsite treatment processesat the unit located in Tarnan.Bunqkul Surabaya.This is a descriptive research, where water samples were drawn as a composite samples, twice aday (morning and afternoon) sampling takes before and after processing the fountain water treatmentunit. Data were collected through laboratory measurements on physical characteristics (smell, color,turbidity, taste, temperature), microbiological parameters (coliform MPNindex), chemical quality (iron andpH) and through organoleptic determination that include smell, color, taste, as well as visual observationson the state of the water fountain and associated treatment unit. Collected data were tabulated andanalyzed as is.Results of physical, microbiological, and chemical examinations showed that parameters were inaccordance with designations in the Ministry of Health Regulation No 492/Menkes/PER/IV/2010. Resultsofthe first and second laboratory analysis indicated decreased levels of color, turbidity, temperature, coliformMPN,iron, pH. However in the second examination the water temperature increased (0.004%).The study concluded that water fountain suitable for consumption. For the maintenance of thewater fountain quality the study suggested that people should wash their hands prior to using the waterfountain and observe the Standard Operating Procedure (SOP).Keywords :drinking water fountain, contaminants, transmission of the disease